Innovation in Digital Arabic Learning: The Effectiveness of the Durusullughoh Application in Enhancing Speaking Skills. - Trio Vangga Nofarmansyah; Zeiburhanus Saleh; Asep Maulana; Syamsul Anam (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Arabic language learning, particularly speaking skills (mahārah kalām), still faces various challenges, such as the use of conventional methods and low student participation. With the advancement of technology, the use of digital media has become an innovative alternative to enhance learning effectiveness. This study aims to determine the effectiveness of using the Durusullughah application in improving the Arabic speaking skills of seventh-grade students at MTsN 5 Jember. This study employed a quantitative approach with a quasi-experimental design using a pre-test and post-test control group model. The sample consisted of two groups: an experimental class and a control class, each comprising 27 students. Data collection techniques included tests, observations, interviews, and documentation, while data analysis was conducted using the Independent Samples t-Test. The results indicate a significant improvement in speaking ability among students in the experimental class compared to the control class, as evidenced by a post-test average score of 77.59 in the experimental class and 64.07 in the control class. Furthermore, the statistical test results showed a Sig. (2-tailed) value of 0.001 (<0.05), indicating a significant difference between the two groups. Thus, it can be concluded that the Durusullughah application is effective in improving students’ Arabic speaking skills.